Innovating ideological work in the new context - NGUYỄN MINH TUẤN (Political Theory Journal, 2026)
The article analyzes the objective urgency of innovating the ideological work of the Communist Party of Vietnam in the context where the digital era and cyberspace have become a “new social space”. Guided by the spirit of the 14th National Party Congress, the article proposes five basic groups of solutions: innovating mindsets and communication methods; perfecting institutions; streamlining the apparatus and standardizing the cadre contingent; and investing in digital infrastructure.
Keywords: digital transformation; ideological work; inovating content; methods of ideologiccal work